2013
DOI: 10.2903/j.efsa.2013.3287
|View full text |Cite
|
Sign up to set email alerts
|

Scientific opinion on the safety and efficacy of iron compounds (E1) as feed additives for all species: iron chelate of amino acids, hydrate, based on a dossier submitted by Zinpro Animal Nutrition Inc.

Abstract: The use of iron chelate of amino acids, hydrate, as source of iron is considered safe for all animal species/categories when used up to the currently authorised maximum content of total iron in complete feed, with the exception of bovines and poultry for which the maximum tolerated level is 450 mg/kg complete feed, and pets, for which the maximum tolerated level is 600 mg/kg complete feed. The FEEDAP Panel is not in the position to derive a maximum safe iron concentration in feed for horses or fish. Consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The safety for consumers of foods derived from animals whose diets were supplemented with iron compounds, including chelate of amino acids, has been reviewed and assessed by the FEEDAP Panel (EFSA FEEDAP Panel, 2013, 2014a,b, 2015, 2016a. It was concluded that no concerns for consumer safety are expected when iron compounds are used up to the EU maximum authorised level in feed.…”
Section: Safety For the Consumermentioning
confidence: 99%
See 1 more Smart Citation
“…The safety for consumers of foods derived from animals whose diets were supplemented with iron compounds, including chelate of amino acids, has been reviewed and assessed by the FEEDAP Panel (EFSA FEEDAP Panel, 2013, 2014a,b, 2015, 2016a. It was concluded that no concerns for consumer safety are expected when iron compounds are used up to the EU maximum authorised level in feed.…”
Section: Safety For the Consumermentioning
confidence: 99%
“…In the absence of specific studies and considering that several iron compounds are recognised as irritants to skin, eyes and mucous membranes (EFSA FEEDAP Panel, 2013, 2014a,b, 2015, 2016a, the product should be considered as a skin, eye and respiratory irritant.…”
Section: Effects On the Eyes And Skinmentioning
confidence: 99%
“…The safety for consumers of foods derived from animals whose diets were supplemented with iron compounds, including chelate of amino acids, has been reviewed and assessed by the FEEDAP Panel (EFSA FEEDAP Panel, 2013a, 2014a,b, 2015, 2016a. The safety for consumers of foods derived from animals whose diets were supplemented with iron compounds, including chelate of amino acids, has been reviewed and assessed by the FEEDAP Panel (EFSA FEEDAP Panel, 2013a, 2014a,b, 2015, 2016a.…”
Section: Safety For the Consumermentioning
confidence: 99%
“…5 EFSA issued an opinion on the safety of the chelated forms of iron, copper, manganese and zinc with synthetic feed grade glycine (EFSA, 2005). In the frame of re-evaluation, EFSA has delivered five opinions on iron-based additives: iron chelate of amino acids, hydrate (EFSA FEEDAP Panel, 2013, 2016a In 2015, the EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) adopted a scientific opinion on the re-evaluation of iron oxides and hydroxides (E 172) as food additives (EFSA ANS Panel, 2015). Following that, the FEEDAP Panel adopted a scientific opinion on the safety and efficacy of iron oxide black, red and yellow for all animal species as colourings in feed (EFSA FEEDAP Panel, 2016b).…”
Section: Additional Informationmentioning
confidence: 99%
“…The opinion is based on data provided by a company involved in the production/distribution of ferric oxide and publicly available literature. In particular, the Opinion on the re-evaluation of iron oxides and hydroxides (E 172) as food additives (EFSA ANS Panel, 2015) and the Opinions on ironbased feed additives (EFSA FEEDAP Panel, 2013, 2014a,b, 2015, 2016a) and on iron oxide black, red and yellow as colourings in feed (EFSA FEEDAP Panel, 2016b) were considered.…”
Section: Assessmentmentioning
confidence: 99%